A Neurophysiological and Neuropsychological Consideration of Mindful Movement: Clinical and Research Implications - Russell, Tamara Anne; Arcuri, Silvia Maria (Frontiers in Human Neuroscience, 2015)
In this article, we present ideas related to three key aspects of mindfulness training: the regulation of attention via noradrenaline, the importance of working memory and its various components (particularly the central executive and episodic buffer), and the relationship of both of these to mind-wandering. These same aspects of mindfulness training are also involved in the preparation and execution of movement and implicated in the pathophysiology of psychosis. We argue that by moving in a mindful way, there may be an additive effect of training as the two elements of the practice (mindfulness and movement) independently, and perhaps synergistically, engage common underlying systems (the default mode network). We discuss how working with mindful movement may be one route to mindfulness training for individuals who would struggle to sit still to complete the more commonly taught mindfulness practices. Drawing on our clinical experience working with individuals with severe and enduring mental health conditions, we show the real world application of these ideas and how they can be used to help those who are suffering and for whom current treatments are still far from adequate.